The effect of political risk and corporate governance on bank stability in the MENA region: Did the Arab Spring uprisings matter? - Ahmed Diab; Mohamed Marie; Adel Elgharbawy; Israa Elbendary (Cogent Business & Management)
This study examines the impact of political risk and corporate governance mechanisms (CGM) on bank stability. The research problem was addressed using a sample of 954 bank-year observations from 14 Middle East and North Africa (MENA) countries during the period 2010–2018 to take into account the effect of the recent uprisings that broke out in the MENA region (i.e., Arab Spring events). This study uses the three-Stage Least-Squares (3SLS) regression method for data analysis. It is found that political stability enhances banks’ financial stability. Regarding the impact of CGM, it is found that board size, board independence, managerial ownership, and audit committee size and meetings significantly and positively affect bank stability. In contrast, board meetings, board gender diversity, CEO duality, and institutional ownership significantly and negatively affect bank financial stability. By dividing the sample into two subsamples (Arab Spring countries and Non-Arab Spring countries), the results revealed that the Arab uprising events significantly affect the relationship between political stability, CGM, and bank stability.